2022
DOI: 10.3390/ma15144997
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Elastic Constants of Refractory Complex Concentrated Alloys Using Machine Learning Approach

Abstract: Refractory complex concentrated alloys (RCCAs) have drawn increasing attention recently owing to their balanced mechanical properties, including excellent creep resistance, ductility, and oxidation resistance. The mechanical and thermal properties of RCCAs are directly linked with the elastic constants. However, it is time consuming and expensive to obtain the elastic constants of RCCAs with conventional trial-and-error experiments. The elastic constants of RCCAs are predicted using a combination of density fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“… 74 Elastic constants: C 11 , C 22 , C 33 , C 12 , C 13 , C 23 , C 44 , C 55 , C 66 1229 binary alloys from Materials Project (DFT) , , VEC, , Regression: random forest (RF) RMSE: 34.61 GPa, MAE: 23.46 GPa, R 2 : 0.779 Bhandari et al. 75 Elastic constants: C 11 , C 12 , C 44 370 MPEAs (DFT) , , , , , VEC, , , name of alloys Regression: gradient boosting regressor (GBR) RMSE: 12.68 GPa, MAE: 9.62 GPa, R 2 : 0.853 Vazquez et al. 76 Elastic constants: C 11 , C 12 , C 44 110 binary and 60 ternary systems (DFT) , , , , , …”
Section: Data Science and Machine Learningmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 Elastic constants: C 11 , C 22 , C 33 , C 12 , C 13 , C 23 , C 44 , C 55 , C 66 1229 binary alloys from Materials Project (DFT) , , VEC, , Regression: random forest (RF) RMSE: 34.61 GPa, MAE: 23.46 GPa, R 2 : 0.779 Bhandari et al. 75 Elastic constants: C 11 , C 12 , C 44 370 MPEAs (DFT) , , , , , VEC, , , name of alloys Regression: gradient boosting regressor (GBR) RMSE: 12.68 GPa, MAE: 9.62 GPa, R 2 : 0.853 Vazquez et al. 76 Elastic constants: C 11 , C 12 , C 44 110 binary and 60 ternary systems (DFT) , , , , , …”
Section: Data Science and Machine Learningmentioning
confidence: 99%
“… 73 The model was reported to have comparable performance to neural network models, having high interpretability at the same time. Other usages include the prediction of various mechanical properties, such as elastic constants, 74 , 75 , 76 hardness, 77 , 78 yield strength, 79 , 80 and Young’s modulus. 80 , 81 , 82 A recent study combined DFT and ML to explore the optimal compositional space of the non-equiatomic MoNbTaTiV system using the element composition as the only feature and identified Ti as the critical factor that could potentially compromise Young’s modulus of the MPEA.…”
Section: Data Science and Machine Learningmentioning
confidence: 99%
“…The dataset was further used to train various ML models, including random forest regressor, gradient boosting regressor, and XGBoost regression models, to predict the mechanical properties of CCAs. For example, the elastic constants in the dataset were used to train those ML models (Bhandari et al, 2022) which were evaluated by the root-mean-squared error, the average coefficient of determination, and mean absolute error. It is found that gradient boosting regressor has higher prediction accuracy on elastic constants.…”
Section: Study Based On the Datasetmentioning
confidence: 99%
“…Other methods also exhibit high accuracy prediction, e.g., a combined ML and CALPHAD technique, an artificial neural network technique (ANN) coupled with experimental data 9 , 10 , 12 , 23 28 . In addition to phase formation of HEAs, machine learning was recently employed to predict the mechanical properties of HEA bulk materials, including microhardness 10 , 27 , yield strength 12 , 23 , dislocation density 12 , elastic modulus 29 , Young’s modulus 30 , hardness 11 , 31 , and elastic constant 32 . These shed light on the ML-based high-throughput screening of HEA materials.…”
Section: Introductionmentioning
confidence: 99%